Marketing de relacionamento: uma análise das variáveis de influência na satisfação dos acadêmicos - Biancheto, Janaine Aparecida Mignoni (2017)
Marketing has proved to be an important competitive tool in administrative evolution. Whereas, the most important is the company to know how to use marketing directing it for its goals and the needs of consumers. The present study has its theme directed towards relationship marketing. The main intention of the research is to verify which of the variables (a) the infrastructure and services offered to the students; (b) confidence in policies and managerial practices; (c) confidence in teachers and expectations, prevail more strongly associated with their relationship with an HEI (higher education institution) by the students of Famper - Faculty of Ampére. The research is classified as qualitative descriptive, having as a population the 544 students of the institution, and the sample used was of 383 respondents academic. To accomplish the aim and to identify which of the variables previously identified are more closely associated with the academic relationship with the institution, the data were presented and analyzed through descriptive statistics and correspondence analysis. With the presentation of the data it was possible to present the profile of the respondents and their evaluations on each variable and to identify the main indexes associated with relationship marketing. It was verified that the variable expectation of the students is the one that has the greatest association with the intention to build a relationship, followed by the variables confidence and services rendered that also demonstrate a good association. The main contribution of this work to the academic environment, was to evoke the relationship marketing as a new possibility of research, mainly, having its direction to the educational institutions. It is suggested that new research addresses customer expectations, exploring this variable and contributing to the use of relationship marketing.